Gene editing reverses arrhythmia susceptibility in humanized PLN-R14del mice: modelling a European cardiomyopathy with global impact. Issue 15 (22nd February 2022) - Dave, Jaydev; Raad, Nour; Mittal, Nishka; Zhang, Lu; Fargnoli, Anthony; Oh, Jae Gyun; Savoia, Maria Elisabetta; Hansen, Jens; Fava, Marika; Yin, Xiaoke; Theofilatos, Konstantinos; Ceholski, Delaine; et al.
Abstract: Aims: A mutation in the phospholamban (PLN) gene, leading to deletion of Arg14 (R14del), has been associated with malignant arrhythmias and ventricular dilation. Identifying pre-symptomatic carriers with vulnerable myocardium is crucial because arrhythmia can result in sudden cardiac death, especially in young adults with PLN-R14del mutation. This study aimed at assessing the efficiency and efficacy of in vivo genome editing, using CRISPR/Cas9 and a cardiotropic adeno-associated virus-9 (AAV9), in improving cardiac function in young adult mice expressing the human PLN-R14del. Methods and results: Humanized mice were generated expressing human wild-type (hPLN-WT) or mutant (hPLN-R14del) PLN in the heterozygous state, mimicking human carriers. Cardiac magnetic resonance imaging at 12 weeks of age showed bi-ventricular dilation and increased stroke volume in mutant vs. WT mice, with no deficit in ejection fraction or cardiac output. Challenge of ex vivo hearts with isoproterenol and rapid pacing unmasked higher propensity for sustained ventricular tachycardia (VT) in hPLN-R14del relative to hPLN-WT. Specifically, the VT threshold was significantly reduced (20.3 ± 1.2 Hz in hPLN-R14del vs. 25.7 ± 1.3 Hz in WT, P < 0.01) reflecting higher arrhythmia burden. To inactivate the R14del allele, mice were tail-vein-injected with AAV9.CRISPR/Cas9/gRNA or AAV9 empty capsid (controls). CRISPR-Cas9 efficiency was evaluated by droplet digital polymerase chain reaction and NGS-based amplicon sequencing. In vivo gene editing significantly reduced end-diastolic and stroke volumes in hPLN-R14del CRISPR-treated mice compared to controls. Susceptibility to VT was also reduced, as the VT threshold was significantly increased relative to controls (30.9 ± 2.3 Hz vs. 21.3 ± 1.5 Hz; P < 0.01). Conclusions: This study is the first to show that disruption of hPLN-R14del allele by AAV9-CRISPR/Cas9 improves cardiac function and reduces VT susceptibility in humanized PLN-R14del mice, offering preclinical evidence for translatable approaches to therapeutically suppress the arrhythmogenic phenotype in human patients with PLN-R14del disease. Graphical Abstract: